INTERAKSI SOSIAL SUKU ANAK DALAM TALANG MAMAK DENGAN MASYARAKAT PENDATANG DI DESA SUO-SUO KECAMATAN SUMAI KABUPATEN TEBO PROVINSI JAMBI - desi intan ratnasari desi intan ratnasari; Afdhal Afdhal (JURNAL BUANA, 2022)
Abstract This study aims to describe how the interaction of the Suku Anak Dalam talang mamak with the local community in Suo-Suo Village, Sumai District, Tebo Regency. This research is a qualitative descriptive study. This research was conducted in Suo-Suo Village, Sumai District, Tebo Regency, Jambi Province. Informants in this study were determined by the purposive sampling technique, namely the sampling technique of data sources with certain considerations. By conducting interviews, observations and documentation. The results of the study revealed that: the interaction of the Suku Anak Dalam talang mamak with the local community, more or less the Suku Anak Dalam talang mamak have come out of their isolation in the forest because inevitably the forest where they live is almost gone because it has been replaced with oil palm and rubber plantations. Indirectly meet with local people and they have to interact. Communication between the local community and the Suku Anak Dalam talang mamak is going well, because the Suku Anak Dalam talang mamak in this area are taught to learn Indonesian so that it is easy for them to communicate.